2012 Ninth International Conference on Information Technology - New Generations 2012
DOI: 10.1109/itng.2012.75
|View full text |Cite
|
Sign up to set email alerts
|

Proposed Model for Social and Collaborative Social Network of Positive Reinforcement: Positive Reinforcement Online Social Network: PRSN

Abstract: In the last years, online social networks (ONSs, online social networks) have grown to become one of the major medias for human beings on the Internet by having a wide distribution and acceptance by users. One of the critical aspects of developing this type of systems is the user interface. For this reason, a modelbased approach is used to allow us collect interaction and collaboration aspects of social networks. Moreover, this paper based on ONSs and model-driven development provides a first approximation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Indisputably, most students use online social networks. For example, a study conducted by [3] already showed that 88% of students used online social networks. A total of 282 K-12 students aged 12 to 18 years participated in that study.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indisputably, most students use online social networks. For example, a study conducted by [3] already showed that 88% of students used online social networks. A total of 282 K-12 students aged 12 to 18 years participated in that study.…”
Section: Introductionmentioning
confidence: 99%
“…A widely accepted definition of a social network site (SNS) is the following: "Platform which allows users to share content, interact and create communities of similar interests" [9]. A positive reinforcement social network (PRSN) is defined in [3] as a social network which allows users to interact with each other and their environment, receiving a reward based on the type and number of actions performed/tracked through/by the system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation